Functionality of arbuscular mycorrhizal fungi in three plant communities in Managed Floristic Reserve San Ubaldo-Sabanalamar, Cuba - Furrazola, Eduardo (2015)
Despite the ubiquity and importance of indigenous arbuscular mycorrhizal fungi (AMF) for plant ecosystems; functioning of indigenus mycorrhizal symbiosis (IMS) and related environmental factors at coastal Caribbean ecosystems remains still scarce. In order to determine functionality of IMS under contrasting land uses and wet seasons from Cuba, the influence of the water stress on some AMF functionality parameters from a semi-natural savannah (NS), a recovered savannah (RS) and an agro-ecosystem (AG) from the Managed Floristic Reserve San Ubaldo-Sabanalamar, Pinar del Rio, Cuba were assessed during two-years. Soil and root samples were collected in April and October, during the dry and wet seasons, respectively, in 2008 and 2010. Four plots in each ecosystem were selected, and five soil sub-samples were randomly collected, bulked, mixed homogeneously and used as the composite sample per plot. The host plant root biomass, arbuscular mycorrhizal colonization of the host plant, density of the intraradical and extraradical AMF mycelia, fungal endophyte biomass and AMF spore density were assessed. The host plant root biomass increased in the NS environment during the dry season, and approximately 12.85g root/dm3 dry soil was recorded. The colonization scores were significantly higher in all environments during the wet season of the second year, with means ranging from 79% to 89%. The extraradical mycelia were significantly more abundant in the dry season of the second year in all environments, with a maximum of 279mg/dm3 in the RS ecosystem. The density of AMF spores was highest in the dry season of the second year for the three studied ecosystems. The RS ecosystem hosted 5 670 spores/100g dry soil. In general, the influence of rainfall seasonality on the function of AMF was stronger than the influence of ecosystem management. The root biomass and extraradical mycelia were high in the dry seasons, suggesting strategies to increase the volume of soil for the mutual benefit of the symbionts. The increase in spore density during the dry seasons appears as an adaptation allowing AMF to survive period of water shortage. This study improves our understanding of the adaptative responses of arbuscular mycorrhizal symbiosis to seasonal variations in soil water availability.